International University Students in Canada: Obtaining the Information Needed for Policy Making - Holdaway, Edward A.; Bryan, Wendy M.; Allan, Wilfred H. (Canadian Journal of Higher Education, 1988)
International university students represent sources of goodwill and benefits for their host countries. Unfortunately, Canada, although still one of the major receiving countries, has seen a substantial decline in international enrolment during the 1980s. Reasons proposed for this decline include differential fees, insufficient financial support, quotas, and employment restrictions. The problems most frequently encountered by international students in Canada involve immigration procedures, accommodation, language, loneliness, and funding. The formulation of policies concerning these problems and other matters relevant to international university students occurs at the federal, provincial, and institutional levels. Even though the main forces driving such policies are cultural, financial, and political, the policies should take into account information about the needs, desires, and experiences of international students. A comprehensive 1986-87 University of Alberta survey of international students served as a case study to demonstrate how research can better inform policy making in this area. Respondents suggested that they would be helped by being allowed to work in Canada while studying and after graduation, which is a federal policy area, and by having more scholarships available to them and differential fees removed, both of which are provincial and institutional policy areas.